Development of Problem Based Learning Worksheets on Class XI Body Defense System Material to Improve Science Literacy - Anisa Maulidiya*; Ixora Sartika Mercuriani (Universitas Syiah Kuala, 2023)
In the 21st century, the use of student worksheets (LKPD) must be integrated with technological developments or electronic media. Teaching materials are known as e-LKPD. The use of e-LKPD teaching materials can be supported by appropriate learning strategies to support the learner-centered learning process, one of which is the problem-based learning model. This study aims to determine the feasibility of e-LKPD based on the PBL model on the immune system material of students of class XI. The type of research carried out is research and development using the ADDIE model. Data collection techniques using non-test in the form of a closed questionnaire. Questionnaires are used to measure the feasibility of e-LKPD media experts, material experts, and biology teachers, as well as student responses. The data analysis technique used is by calculating the average value (mean) and converted to determine the feasibility category. The results of this study show that the average e-LKPD product feasibility assessment results by material experts 92,192 include the very feasible Category, the average e-LKPD product feasibility assessment by media experts 85.1 including the category is very feasible, the e-LKPD product feasibility assessment by biology teachers 98.24357 includes the very feasible category, and the product feasibility assessment results based on student Responses 96,375 belong to the very feasible category. The conclusion of this study shows that PBL-based e-LKPD teaching materials on body defense system materials are suitable for use in biology learning for class XI students